A dynamic stochastic pension fund model 2 - Ziemba, William (Henry Stewart Talks, 2013)
Portfolio theory and practice, Effect of paramater errors, Convex risk measures, Scenario optimization, Asset liability management, Pension funds, Retirement, Siemens Austria pension fund